Factors Influencing Childhood Immunization Defaulters in Sabah, Malaysia - Azhar S, Shamsul; K, Nirmal; S, Nazarudin; H, Rohaizat; A, Azimatun Noor; H, Rozita (IIUM Medical Journal Malaysia, 2012)
Introduction: The purpose of this study was to determine the prevalence of defaulters of immunization, and their associated risk factors among children age 12 to 24 months. Materials and Methods: A cross-sectional study was conducted in all government’s maternal child health clinics in District of Kota Kinabalu, Sabah. Data was collected using a standardised questionnaire from July to November 2006. Results: The prevalence rate for defaulting immunization was 16.8% from the 315 respondents. Bivariable analysis showed various significant factors associated with defaulters such as mother’s employment status, family mobility, transportation and cost. Nonetheless, multivariable analysis showed only mother’s age, mother employment status and family size were the significant predictors for defaulting immunization. Immunization that had the highest rate of defaulters was DPT–OPV booster dose (56.6%), followed by MMR immunization (43.4 %) and DPT-Hib/OPV and Hep B third dose (37.7%).Conclusion: Employed mothers with bigger family size should be more closely monitored and advised to reduce the chance of defaulting on the immunization. Health promotion activities also should focus to these groups of mothers.